The Development of a Stigma Support Intervention to improve the Mental Health of Family Carers of Autistic Children: Suggestions from the Autism Community - Lodder, Annemarie; Papadopoulos, Chris; Randhawa, Gurch (European Journal of Mental Health, 2019)
Parents and family carers of autistic children report poorer mental health than any other parents. Stigma surrounding autism plays a significant role in the mental health of family carers of autistic children, often leaving families feeling isolated. Yet there are currently no interventions available to support families with stigma. In order to guide the design and development of an intervention to improve the psychological well-being of parents and carers of autistic children by addressing the stigma they may experience, we surveyed the autism community (n = 112) about their views and suggestions to make such intervention more successful. The thematic analysis of the qualitative responses revealed that respondents wished for public awareness to be raised and suggested that education would be the key to this. Respondents also – recommended that parental self-esteem and self-compassion skills should be increased and that they would benefit from ‘ready-made’ phrases or information available to react to instances of stigma from the public, other family members, and professionals. The autism community provided valuable suggestions to be incorporated in the design of a stigma support intervention for parents of autistic children, in order to improve their mental health and caregiving abilities.